FUNGSI MANAJEMEN KEUANGAN PENDIDIKAN DI SD NEGERI KALONGAN 01 - Apriliya, Nurul; Ngatijah, Ngatijah; Nurkolis, Nurkolis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Educational institutions have a responsibility to realize the ideals of educating the nation's life and forming a virtuous national personality, so that education can be defined as an important factor in realizing quality human resources (HR). This research is to describe the financial management of education at SD Negeri Kalongan 01. The research used is descriptive qualitative which refers to an explanation of Educational Financing Management. With this research, the author will use descriptive research methods through a qualitative approach. The subjects of this research were the principal, property, teachers, parents and the school committee. Data collection was obtained through interviews, observation and documentation. Financial management and financing principles that must be applied include transparency, accountability, effectiveness, efficiency and fairness. The research results show (1) Financial planning education is made into a 1 year budget. (2) The implementation of financing is carried out in accordance with the RAPBS and is reported every three months. (3) Monitoring and evaluation of education financing is carried out periodically.